2015
DOI: 10.1002/jms.3708
|View full text |Cite
|
Sign up to set email alerts
|

MALDI imaging reveals lipid changes in the skin of leprosy patients before and after multidrug therapy (MDT)

Abstract: Leprosy still represents a health problem in several countries. Affecting skin and peripheral nerves, it may lead to permanent disabilities. Disturbances on skin lipid metabolism in leprosy were already observed; however, the localization and distribution of lipids could not be accessed. The role of lipids on infectious disease has been fully addressed only recently, as they directly influence immune response. Matrix-assisted laser desorption/ionization imaging mass spectrometry provides a powerful tool to loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…Spectra from the 1st layer are featured with ceramide cluster mainly resident between 600 and 700 m/z, while spectra from the 56th layer are dominated by phosphatidylcholine (PC) and phosphatidylethanolamine (PE) between 700 and 800 m/z. Many other lipids such as phosphatidylglycerol (PG), phosphatidylserine (PS), sphingomyelin (SM), diacylglycerol (TAG), and triglyceride (TG) were potentially detected in both spectra, which is comparable to lipid classes found in previous skin imaging experiments using LDI and MALDI [9,39]. Although further structural information (e.g., location of double bonds) requires fragmentation with tandem mass spectrometry (MS/MS) for isobaric lipid determinations, putative identifications at the molecular formula level are sufficient for the demonstration of 3D imaging without the need for cryosectioning.…”
Section: Molecular Annotations Of Lipids In Skinsupporting
confidence: 68%
“…Spectra from the 1st layer are featured with ceramide cluster mainly resident between 600 and 700 m/z, while spectra from the 56th layer are dominated by phosphatidylcholine (PC) and phosphatidylethanolamine (PE) between 700 and 800 m/z. Many other lipids such as phosphatidylglycerol (PG), phosphatidylserine (PS), sphingomyelin (SM), diacylglycerol (TAG), and triglyceride (TG) were potentially detected in both spectra, which is comparable to lipid classes found in previous skin imaging experiments using LDI and MALDI [9,39]. Although further structural information (e.g., location of double bonds) requires fragmentation with tandem mass spectrometry (MS/MS) for isobaric lipid determinations, putative identifications at the molecular formula level are sufficient for the demonstration of 3D imaging without the need for cryosectioning.…”
Section: Molecular Annotations Of Lipids In Skinsupporting
confidence: 68%
“…121,122 It has been found that, overall, leprosy patients have increased phospholipidid metabolism in skin lesions and polyunsaturated fatty acid metabolism in both their serum and skin lesions, which are, however, more prominent in multibacillary patients. 117,123 A metabolomics analysis demonstrated an augmentation in omega-3 and omega-6 polyunsaturated fatty acids, especially in linoleic (n-6) and docosapentaenoic (n-3/n-6) acids in skin lesions, as well as in the intermediate and end products of lipid mediator biosynthesis in serum. After the completion of multidrug therapy, lipid mediator concentrations decreased.…”
Section: Lipid Accumul Ati On a S A S Tr Ategy For Mitochondrial S H Utdownmentioning
confidence: 99%
“…Furthermore, MSI offers potential for biomarker discovery 38 as analysis can be performed untargeted, with statistical interrogation to discern molecular changes between tissue regions. MSI has grown in popularity as a tool to study host-pathogen interactions and has been used to find molecules differentially regulated due to infection 15, 18–22, 39–41 .…”
Section: Discussionmentioning
confidence: 99%